Accounting of Bugis Tribe Marriages in Labuhan Lombok Village: Ethnographic Study - Tari Indaryani; Ayudia Sokarina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to understand the Bugis tribe's marriage accounting for migrants in Labuhan Lombok. This research uses an interpretive and ethnographic paradigm as research methodology. Data collection techniques were carried out by observation and interviews. Interviews were conducted with four informants consisting of the bride and groom, the woman's family and the local community. The results of this research show that the series of Bugis wedding processions consisting of Memanu-manu, Massuro, MappatuAda, Mangolli, Cemme, Mappanre Temme, Mappacci, Mappabotting, Reception, and Mapparola contain the values of affection, steadfastness, honesty and family values. . The implications of this research can develop cultural accounting practices that are relevant for Bugis tribal migrants in the context of marriage.